2016
DOI: 10.11113/jt.v78.8146
|View full text |Cite
|
Sign up to set email alerts
|

ANALYSIS OF BIOACTIVE COMPOUNDS OF Caulerpa recemosa, Sargassum sp. AND Gracillaria verrucosa USING DIFFERENT SOLVENTS

Abstract: This study aimed to analyze the bioactive compounds of Caulerpa recemosa, Sargassum sp., and Gracillaria verrucosa from Makssar Strait using three different solvents i.e. acetone, ethanol , and methanol. Samples of the seaweed C. recemosa collected from marine waters of Takalar regency, while Sargassum sp. and G. verrucosa were collected from marine waters of Pangkep regency which is part of the Makassar Strait. Seaweed crude extract qualitatively analyzed using Thin Layer Chromatography (TLC). The treatment a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 8 publications
(5 reference statements)
0
2
0
3
Order By: Relevance
“…GVM and GVE had the highest total polyphenol and flavonoid contents, respectively, whereas GVW had the lowest. Rusli et al [49] observed that methanol extracts of GV, Sargassum sp., and Caulerpa recemosa had the highest polyphenol content, followed by ethanol and acetone extracts. Similarly, Farbin et al [50] indicated that organic solvents are more efficacious than water for polyphenol extraction.…”
Section: The Total Polyphenol and Flavonoid Content Of Gv Extractsmentioning
confidence: 99%
“…GVM and GVE had the highest total polyphenol and flavonoid contents, respectively, whereas GVW had the lowest. Rusli et al [49] observed that methanol extracts of GV, Sargassum sp., and Caulerpa recemosa had the highest polyphenol content, followed by ethanol and acetone extracts. Similarly, Farbin et al [50] indicated that organic solvents are more efficacious than water for polyphenol extraction.…”
Section: The Total Polyphenol and Flavonoid Content Of Gv Extractsmentioning
confidence: 99%
“…Analysis of fat content of catfish meatballs. The same notation shows a value that is not significantly different at the 5% significance level with the Duncan test Jurnal Kelautan dan Perikanan Terapan, 5 (1), 2022, 11-16 DOI: http://dx.doi.org/10.15578/jkpt.v5i1.10951 protein dalam bakso juga semakin banyak (Rusli et al, 2017). Menurut Trisnawati & Nisa (2015), karagenan mempunyai sifat mengikat atau memerangkap air dalam matriks gel sehingga dapat mencegah kehilangan protein larut dalam air.…”
Section: Kadar Proteinunclassified
“…Penurunan daya larut film cenderung berbanding terbalik dengan peningkatan konsentrasi CMC. Hal ini karena padatan terlarut yang berasal dari bahan dasar pembuatan edible film dan meningkatnya jumlah molekul dalam larutan (Rusli, Metusalach, Salengke, & Tahir, 2017). Nilai kelarutan tertinggi 48% pada CMC 5% mengindikasikan film mudah terurai dan digunakan untuk produk siap makan seperti sosis sapi, kelarutan tinggi menunjukkan ketahanan terhadap air lebih rendah namun lebih mudah larut (Fardhyanti & Julianur, 2015).…”
Section: Gambar 3 Pengaruh Konsentrasi Cmc Terhadap Solubility Ediblunclassified